Policy analysis with Melitz-type gravity model: Evidence from Kyrgyzstan - Barchynai Kimsanova; Thomas Herzfeld (Journal of Asian Economics, 2022)
Several governments worldwide aim at fostering agricultural productivity growth by providing investment support. However, the policy's effect on trade for middle- and low-income countries has not been analyzed so far. This paper analyzes the impact of agricultural policies (credit subsidies and tariffs) on agricultural trade flows by modifying a Melitz-type structural gravity model for a small and open economy. According to the theory, trade flows are expected to increase with credit subsidies and decrease with partners' applied tariff rates. We analyze bilateral agricultural trade flows between Kyrgyzstan and its 69 trading partners from 2007 to 2018 to test our theoretical findings. Applying the Poisson pseudo maximum likelihood estimator, we find that credit subsidies effectively increase international trade flows while applied tariffs imposed on agricultural products reduce Kyrgyzstan's export substantially. These results can be applied to similar economies with publicly available data where small budgetary efforts drive trade expansion.
Keywords: F10; F13; F14; 330; gravity model; general equilibrium effects; tariffs; subsidies